The Evangelical-Lutheran Church in South Africa: an introduction to its archival resources held at the Lutheran Theological Institute (LTI) Library, and the challenges facing this archive (Part One). - Garaba, Francis (Missionalia, 2014)
This article consists of two parts, the first dealing with the contents of the Lutheran Theological Institute Archive in the context of the history of the Lutheran church in South Africa, the second covering the practicalities of the management of this archive. This part (Part One) provides an account of the manuscript collections in the custody of the LTI library, situated in Pietermaritzburg, South Africa. The article attempts to alert the reader to the primary material that is available for developing a deeper understanding of the history of the Lutheran church in Southern Africa and it thereby serves as an indirect public outreach campaign to unlock and publicise the contents of the archive. It should be noted here that only about half of the archival papers held at the LTI have thus far been processed. This is an ongoing project which, it is hoped, will be completed in 2016. Where pertinent, the holdings of the LTI Archive as well as the as-yet unsorted papers are indicated below in italics, in order to give readers an indication of the nature and extent of the collection.